2004
DOI: 10.1162/153535004773861705
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Dynamics of Gene Expression in the Living Mouse

Abstract: Reporter genes can monitor the status and activity of recombinant genomes in a diverse array of organisms, from bacteria and yeast to plants and animals. We have combined luciferase reporter genes with a conditional gene expression system based on regulatory elements from the lac operon of Escherichia coli to visualize the dynamics of gene expression in realtime in the living mouse. Using this technology, we have determined the rate of gene induction and repression, the level of target gene activity in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…In M mice, MGF was expressed using the HD locus promoter which was modified to include lac operators and in R mice, the human β-actin promoter was used to drive the Lac-I gene expression. Both transgene constructions have been previously utilized in our studies [17, 18] when overexpressed MGF was identified in spinal cord and hippocampal neurons (Fig. 1b and c).…”
Section: Methodsmentioning
confidence: 99%
“…In M mice, MGF was expressed using the HD locus promoter which was modified to include lac operators and in R mice, the human β-actin promoter was used to drive the Lac-I gene expression. Both transgene constructions have been previously utilized in our studies [17, 18] when overexpressed MGF was identified in spinal cord and hippocampal neurons (Fig. 1b and c).…”
Section: Methodsmentioning
confidence: 99%
“…The present study has tested a modified bacterial lac operon system, developed originally by Scrable and colleagues [6][8], to reversibly control gene expression in the vasculature in vivo. We show that this system can be used to reliably repress gene expression selectively in the vascular endothelium, through the use of the modified endothelial specific promoter TIE2 [11].…”
Section: Discussionmentioning
confidence: 99%
“…Mice from this strain were developed to be homozygous for a transgene that expresses the LacI R inhibitor protein under control of the ubiquitous β-actin promoter [8]. The heterozygous LacI R strain was a generous gift from Professor Heidi Scrable, University of Virginia, Charlottesville, Virginia, USA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations